2016
DOI: 10.4103/0974-9233.164621
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of utilization of eye care services in a rural adult population of a developing country

Abstract: Purpose:To describe the factors that determine the utilization of eye care services in a rural community in South-Western Nigeria.Methods:A descriptive cross-sectional survey using a multistage sampling technique was conducted. The main outcome measure was self-reported previous consultation of an orthodox medical facility for eye care.Results:The study sample included 643 participants. Only 122 (19%) respondents had previously visited orthodox facilities in search of eye care and 24% of those with presenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
41
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 27 publications
9
41
3
Order By: Relevance
“…This demonstrates a generally good eye care seeking behaviour among the participants. This finding however conflicts with those of Ebeigbe and Ovenseri-Ogbomo, Robin et al and Olusanya et al [7][8][9], in which majority of the participants had previously not gone for an eye examination in a hospital before. There was no statistically significant difference in gender utilization of eye care services (p=0.204), even though female participants were more than male participants.…”
Section: Discussioncontrasting
confidence: 56%
“…This demonstrates a generally good eye care seeking behaviour among the participants. This finding however conflicts with those of Ebeigbe and Ovenseri-Ogbomo, Robin et al and Olusanya et al [7][8][9], in which majority of the participants had previously not gone for an eye examination in a hospital before. There was no statistically significant difference in gender utilization of eye care services (p=0.204), even though female participants were more than male participants.…”
Section: Discussioncontrasting
confidence: 56%
“…As expected, education was found to have a positive influence on the choice of care giver in this study. This trend agrees with other studies [8], [9], [15], [17], [21] that observed that educated individuals had a greater likelihood of seeking orthodox eye care. However, we found out paradoxically that educational level did not influence the source of obtaining spectacles as majority of both those with less education and those with higher education used un-prescribed spectacles obtained from the market or obtained as a gift.…”
Section: Discussionsupporting
confidence: 83%
“…[17]- [21] This agrees with our finding as only 31.2 % of our respondents patronized the available eye clinic for treatment and 24.5% for spectacles. This is in spite of the fact that the Nchokko village is part of the Igbeagu community, which hosts the community eye care services of the department of Ophthalmology of FETHA, and is only 20 minutes drive away from Abakaliki the state capital where the teaching hospital is situated.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations